Keanekaragaman Serangga Hama dan Musuh Alami pada Pertanaman Selada (Lactuca sativa L.) Organik - Laura Ramitum; Akhmad Gazali; Rila Rahma Apriani (Universitas Lambung Mangkurat, 2022)
The diversity of insect pests and natural enemies can be influenced by external factors, where they can live with a certain temperature range, either at the maximum, optimum or minimum levels. There are differences in abiotic data with diversity in organic and inorganic soils, ranging from data on rainfall, humidity and soil pH. This is thus influenced by conditions around the research area. Environmental factors, both internal and external, can influence the development of insect pests and natural enemies on the land, such as by the factor of too high rainfall, unstable humidity and soil pH which can also affect the development of insects, especially insects on the soil surface (Noviar, 2007). This research was conducted at the Agroecotechnology Experimental Garden, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan from June - August 2020. This study used direct observation methods on plants. With the treatment of giving chicken manure and giving inorganic fertilizers (Urea, SP-36 and KCL). Observations of the diversity of pests and natural enemies in organic lettuce were carried out at 2 weeks after planting (MST) until the age of harvest. Time of applying fertilizer at the beginning of soil cultivation. The experimental unit was in the form of two lettuce beds with a size of 2 mx 5 m for each. The results of observations of insect pests and natural enemies in lettuce (Lactuca sativa L.) with the application of insecticides showed the number of 7 orders contained. For the number of families there are 20 and the number of individuals there are 428